Polyp flats, a new system for experimenting with jellyfish polyps, with insights into the effects of ocean acidification - Olariaga, Alejandro; Fernández-Guallart, E.; Fuentes, Veronica; López-Sanz, Àngel; Canepa, Antonio; Movilla, Juan Ignacio; Bosch Belmar, Mar; Calvo, Eva María; Pelejero, Carles (Limnology and Oceanography: Methods, 2014)
11 pages, 6 figures, 4 tables Research interest on jellyfish has grown exponentially over the last years and studies focusing on the biology and ecology of the jellyfish polyp stage are being recognized as crucial in understanding jellyfish proliferations. Due to the difficulty of conducting in situ work with jellyfish polyps, laboratory experiments are the most used approach. Here, we describe the design and successful testing of a new system that allows continuous seawater renewal while keeping constant the selected physicochemical conditions of the water throughout the experiment in contrast to closed systems used previously. As a first test, we started an experiment to assess the effects of ocean acidification on the growth and development of jellyfish polyps of Aurelia sp. This new design demonstrated high precision in maintaining constant conditions (pH, temperature, and flow rates) among the replicates of each treatment, and ensured excellent conditions for jellyfish polyp survival. All together it has shown to be an effective platform to assess the effect of environmental variables on the growth and development of jellyfish polyps. © 2014, by the American Society of Limnology and Oceanography, Inc. The construction of the system was funded by the European Commission through the LIFE + program CUBOMED project, by the Spanish Ministry of Economy and Competitiveness through projects ACDC (CTM2009-08849) and MANIFEST (CTM2012-32017) and by Generalitat de Catalunya through the Marine Biogeochemistry and Global Change research group (grant 2009SGR142). E.F. Guallart was funded by CSIC through a JAE-Pre grant, and A. Canepa was funded by CONICYT (PFCHA/Doctorado al Extranjero 4ª Convocatoria, 72120016) All developmental work in this study was performed at the Experimental Aquaria Zone (ZAE) of Institut de Ciències del Mar (ICM-CSIC) Peer Reviewed